Canine Transmissible Venereal Tumors: Aspects Related to Programmed Cell Death - Stockmann, Daniela; Ferrari, Heitor F.; Andrade, Alexandre L.; Lopes, Rodrigo A.; Cardoso, Tereza C.; Luvizotto, Maria C. R. (Brazilian Journal of Veterinary Pathology, 2011)
Canine transmissible venereal tumor (CTVT) is a neoplasm transmitted by the physical transfer of viable tumor cells by direct contact with injured skin and/or mucous tissue. These cells can transpose across histocompatibility barriers into unrelated hosts. This review focuses on the biology of apoptosis and the interaction of proteins involved in this process, as well as p53, p63 and the antiapoptotic protein Bcl-2. As such, this disease offer unique opportunity to study the biology of transplantable tumours and the interaction of proteins involved in apoptosis process and the prognosis of CTVT.